The Basic Aspects of the Hyman Minsky’s Financial Instability Hypothesis - Rozmainsky, I. (Економічний вісник Донбасу, 2017)
This paper considers the basic aspects of the financial instability hypothesis developed by Hyman Minsky. This conception has become very pertinent due to the events concerned with the Great Recession. The author shows both links between Keynes’s theory and Minsky approach and Post Keynesian “spirit” of the described hypothesis. The special role of uncertainty and money has been emphasized. The paper shows that the hypothesis provides an understanding of how the contemporary market capitalist economy endogenously becomes “financially fragile” and thus prone to crises. The author demonstrates that the Great Recession can be treated as a consequence of the processes described by the financial instability hypothesis. У статті розглядаються основні аспекти гіпотези фінансової нестабільності, розробленої Хайманом Мінскі. Ця концепція стала дуже актуальною через події, пов'язані з Великою рецесією. Автор роботи демонструє як зв'язки між теорією Кейнса і підходом Мінскі, так і посткейнсіанський «дух» описуваної гіпотези. Підкреслюється особлива роль невизначеності і грошей. Показано, що гіпотеза дозволяє зрозуміти, як сучасна ринкова капіталістична економіка ендогенно стає «фінансово тендітною» і, таким чином, схильною до криз. Автор демонструє, що Велику рецесію можна трактувати як наслідок процесів, що описуються гіпотезою фінансової нестабільності. В статье рассматриваются основные аспекты гипотезы финансовой нестабильности, разработанной Хайманом Мински. Эта концепция стала очень актуальной из-за событий, связанных с Великой рецессией. Автор работы демонстрирует как связи между теорией Кейнса и подходом Мински, так и посткейнсианский «дух» описываемой гипотезы. Подчеркивается особая роль неопределенности и денег. В статье показано, что гипотеза позволяет понять, как современная рыночная капиталистическая экономика энгдогенно становится «финансово хрупкой» и, таким образом, подверженной кризисам. Автор демонстрирует, что Великую рецессию можно трактовать как следствие процессов, описываемых гипотезой финансовой нестабильности.